Antibacterial and antibiofilm activities of kaffir lime essential oils and their active constituents against Staphylococcus aureus focusing on sortase A - Chayapol Pontanayodsakorn; Chatchakorn Eurtivong; Pimsumon Jiamboonsri (Heliyon, 2025)
infection.
Keywords: Biochemical and Structural Characterization; Essential Oils and Antimicrobial Activity; Phytochemistry and Biological Activities